Rancang Bangun Sistem Radar Menggunakan Mikrokontroler untuk Pendeteksi Objek Otomatis - Nicole Mahdi Wardana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Radar (Radio Detection and Ranging) is a technology that has been widely used in various fields. fields. Such as ship navigation, aviation industry, air traffic surveillance, weather monitoring, and security applications. air traffic control, weather monitoring, and security applications. Radar utilizes electromagnetic signals to detect, track, and determine the distance and position of surrounding objects. of objects in the vicinity.